L‐glutamine Improves Skeletal Muscle Cell Differentiation and Prevents Myotube Atrophy After Cytokine (TNF‐α) Stress Via Reduced p38 MAPK Signal Transduction. Issue 12 (14th April 2016) - Girven, Matthew; Dugdale, Hannah F.; Owens, Daniel J.; Hughes, David C.; Stewart, Claire E.; Sharples, Adam P.
Abstract : Tumour Necrosis Factor‐Alpha (TNF‐α) is chronically elevated in conditions where skeletal muscle loss occurs. Asl ‐glutamine can dampen the effects of inflamed environments, we investigated the role ofl ‐glutamine in both differentiating C2C12 myoblasts and existing myotubes in the absence/presence of TNF‐α (20 ng · ml −1 ) ± l ‐glutamine (20 mM). TNF‐α reduced the proportion of cells in G1 phase, as well as biochemical (CK activity) and morphological differentiation (myotube number), with corresponding reductions in transcript expression of: Myogenin, Igf‐I, and Igfbp5 . Furthermore, when administered to mature myotubes, TNF‐α induced myotube loss and atrophy underpinned by reductions in Myogenin, Igf‐I, Igfbp2, and glutamine synthetase and parallel increases in Fox03, Cfos, p53, and Bid gene expression. Investigation of signaling activity suggested that Akt and ERK1/2 were unchanged, JNK increased (non‐significantly) whereas P38 MAPK substantially and significantly increased in both myoblasts and myotubes in the presence of TNF‐α. Importantly, 20 mMl ‐glutamine reduced p38 MAPK activity in TNF‐α conditions back to control levels, with a corresponding rescue of myoblast differentiation and a reversal of atrophy in myotubes.l ‐glutamine resulted in upregulation of genes associated with growth and survival including; Myogenin, Igf‐Ir, Myhc2 & 7, Tnfsfr1b, Adra1d, and restored atrophic gene expression of Fox03 back to baseline in TNF‐α conditions. In conclusion, l ‐glutamine supplementation rescued suppressed muscle cell differentiation and prevented myotube atrophy in an inflamed environment via regulation of p38 MAPK.l ‐glutamine administration could represent an important therapeutic strategy for reducing muscle loss in catabolic diseases and inflamed ageing. J. Cell. Physiol. 9999: 231: 2720–2732, 2016. © 2016 Wiley Periodicals, Inc. Abstract : l ‐glutamine supplementation rescued suppressed muscle cell differentiation and prevented myotube atrophy in an inflamed cytokine environment (TNF‐α) via regulation of p38 MAPK singaling.l ‐Glutamine supplementation evoked reductions in p38 MAPK following extensive increases after TNF‐α administration. This was associated with downstream regulation of gene transcription associated with growth and survival including increased; Myogenin, Igf‐Ir, Myhc2 & 7, Tnfsfr1b, Adra1d, and reduced atrophic gene expression of Fox03 back to baseline in TNF‐α conditions.l ‐glutamine administration could represent an important therapeutic strategy for reducing muscle loss in catabolic diseases and inflamed ageing.